The final frontier: what is distinctive about the bioethics of space missions? The cases of human enhancement and human reproduction - Szocik, K; Reiss, MJ (Springer Science and Business Media LLC, 2022)
We examine the bioethical issues that arise from long-duration space missions, asking what there is that is distinctive about such issues. We pay particular attention to the possibility that such space missions, certainly if they lead to self-sustaining space settlements, may require human enhancement, and examine the significance of reproduction in space for bioethics. We conclude that while space bioethics raises important issues to do with human survival and reproduction in very hazardous environments, it raises no issues that are distinct from those in terrestrial bioethics. Rather, space bioethics raises extreme versions of bioethical issues that are already found in the military, when working in extreme environments (such as Antarctica), or when living in circumstances (such as in prison) where one’s autonomy is severely curtailed.